2009
DOI: 10.1039/b903024g
|View full text |Cite
|
Sign up to set email alerts
|

Surface aggregate structure of nonionic surfactants on silica nanoparticles

Abstract: The self-assembly of two nonionic surfactants, pentaethylene glycol monododecyl ether (C 12 E 5 ) and n-dodecyl-ß-maltoside (ß-C 12 G 2 ), in the presence of a purpose-synthesized silica sol of uniform particle size (diameter 16 nm) has been studied by adsorption measurements, dynamic light scattering and small-angle neutron scattering (SANS) using a H 2 O/D 2 O mixture matching the silica, in order to highlight the structure of the surfactant aggregates. For C 12 E 5 strong aggregative adsorption onto the sil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
113
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(130 citation statements)
references
References 38 publications
16
113
1
Order By: Relevance
“…The adsorption of b-C 12 G 2 to negatively charged silica has been shown to be weak. 35,36 The deformation of the bubble at the same nanoparticle concentration with varying b-C 12 G 2 concentration is illustrated in Fig. 4a , respectively.…”
Section: In the Presence Of Non-ionic Surfactantsmentioning
confidence: 99%
“…The adsorption of b-C 12 G 2 to negatively charged silica has been shown to be weak. 35,36 The deformation of the bubble at the same nanoparticle concentration with varying b-C 12 G 2 concentration is illustrated in Fig. 4a , respectively.…”
Section: In the Presence Of Non-ionic Surfactantsmentioning
confidence: 99%
“…For instance, for the surfactant penta(ethyleneglycol) monododecylether (C 12 E 5 ) it was recently found that discrete surface micelles are formed on silica nanoparticles, 14,16 although flat bilayer aggregates are preferred at planar silica surfaces. 6,7 At even weaker anchoring energies, surface micelles may be disfavoured against micelles in solution, implying that little or no adsorption occurs, as in the case of dodecyl maltoside (b-C 12 G 2 ) at silica nanoparticles.…”
Section: -18mentioning
confidence: 99%
“…6,7 At even weaker anchoring energies, surface micelles may be disfavoured against micelles in solution, implying that little or no adsorption occurs, as in the case of dodecyl maltoside (b-C 12 G 2 ) at silica nanoparticles. 14 Here, we study the influence of particle size and surface modification on the adsorption of the surfactant C 12 E 5 at silica nanoparticles. The particles were synthesized by a modified St€ ober method 19 yielding particles of narrow size distribution down to the 10 to 50 nm size range which was of interest in this study.…”
Section: -18mentioning
confidence: 99%
See 1 more Smart Citation
“…While the free volume between stabilizer chains would suggest that such an arrangement is not possible, such a form factor has recently been used to describe CV-SANS data measured for the adsorption of nonionic surfactant micelles on silica nanoparticles in water. 44 The scattering from AOT-D 34 with PMMA latexes in PMMA-matched solvent has been fit using a "raspberry" model, which is appropriate for Pickering emulsions or nanocomposite raspberry particles. 45 As in Figure 7, the core dimensions were fixed, and parameters describing the inverse micelles were allowed to vary (r; φ ; and χ, the fraction of interfacial area covered).…”
Section: Pmma Latexes With Aotmentioning
confidence: 99%